Stress, Satisfaction and Militancy among Canadian Physicians - Burke, Ronald (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1995)
The present study utilized a stressor-strain framework to understand physician militancy in Canada. Data were collected from 2,584 physicians in 1986 using questionnaires. Four militant attitudes or activities were considered: approval of binding arbitration in the event of deadlocks in fee negotiations with governments, approval of withdrawal of services in the event of inadequate income settlements, approval of the reconstitution of medical associations as labour unions, and whether they had participated in an organized job action involving withdrawal of services.